Neurobiology of the Milgram Obedience Experiment - Eren Yavuz, Kudret; Tarlacı, Sultan (Journal of NeuroPhilosophy, 2023)
This manuscript presents a comprehensive review of the neurobiology underlying the Milgram Obedience Experiment, a cornerstone in understanding human behavior under authority. Beginning with an examination of traumatic historical events, particularly the Holocaust, the manuscript delves into the psychological underpinnings of obedience. It discusses how individuals, like Adolf Eichmann, rationalized their actions as mere adherence to orders, a phenomenon later empirically studied by Stanley Milgram. Milgram’s experiments, conducted at Yale University, demonstrated a startling willingness among ordinary people to inflict harm when instructed by an authority figure, with a significant proportion of participants administering what they believed were lethal electric shocks to others. The review further explores the neurobiological aspects of obedience, emphasizing the role of mirror neurons and empathetic responses. It highlights how obedience to authority can diminish empathetic responses and alter the neural processing of actions and consequences. This diminished sense of agency and responsibility when following orders is contrasted with situations where individuals act on their own volition, shedding light on the complex interplay between authority, morality, and neurobiology. In conclusion, this review not only provides a deep insight into Milgram’s obedience experiments but also extends the understanding of the neurobiological mechanisms that drive human behavior in contexts of authority and obedience. It underscores the intricate balance between individual autonomy and susceptibility to external influences, a balance that is crucial in understanding both historical events and contemporary societal dynamics.